Relationship between tumor biomarkers and efficacy in MARIANNE, a phase III study of trastuzumab emtansine ± pertuzumab versus trastuzumab plus taxane in HER2-positive advanced breast cancer - Perez, Edith A.; de Haas, Sanne Lysbet; Eiermann, Wolfgang; Barrios, Carlos H.; Toi, Masakazu; Im, Young-Hyuck; Conte, Pier Franco; Martin, Miguel; Pienkowski, Tadeusz; Pivot, Xavier B.; Burris, Howard A.; Stanzel, Sven; et al. (BMC cancer, 2019)
Background The phase III EMILIA and TH3RESA trials demonstrated clinical benefits of trastuzumab emtansine (T-DM1) therapy in patients with previously treated HER2-positive metastatic breast cancer (MBC). Data from these and other trials showed that T-DM1–associated survival benefits were observed across biomarker subgroups tested in these trials. Prespecified, exploratory analyses of the phase III MARIANNE study examined the effects of HER2-related biomarkers on PFS in patients administered T-DM1 in the first-line MBC setting. Methods In MARIANNE, patients with previously untreated HER2-positive MBC were randomized (1:1:1) to trastuzumab plus taxane, T-DM1 plus placebo, or T-DM1 plus pertuzumab. Biomarker subgroups included HER2 and HER3 mRNA expression levels (≤median vs. >median), HER2 staining intensity (IHC 3+ vs. 2+ vs. 0/1+), PIK3CA status (mutated vs. non-mutated), PTEN H-score (≤median vs. >median), and PTEN protein expression level (0 vs. 1+ vs. 2+ vs. 3+ vs. 4+). PFS was analyzed descriptively for each subgroup using Kaplan–Meier methodology. Additional exploratory post-hoc analyses evaluated the effects of HER2 heterogeneity. Multivariate analyses were also performed. Results Median PFS was numerically longer for patients with HER2 mRNA levels >median versus ≤median across treatment arms. In general, there were no predictive biomarkers of benefit for either T-DM1 treatment arm; most hazard ratios were close to 1 with wide confidence intervals that included the value 1. Focal HER2 expression (IHC 3+ or IHC 2+) was present in 3.8% of patients and was associated with numerically shorter PFS in the T-DM1–containing treatment arms versus trastuzumab plus taxane. Compared with non-mutated PIK3CA , mutated PIK3CA was associated with numerically shorter median PFS across treatment groups. Post-hoc multivariate analysis showed HER2 mRNA expression and mutated PIK3CA were prognostic for PFS ( P ≤ 0.001 for both biomarkers). Conclusions In MARIANNE, biomarkers related to the HER2 pathway did not have predictive value for PFS when comparing T-DM1 (with or without pertuzumab) with trastuzumab plus taxane. However, HER2 mRNA level and PIK3CA mutation status showed prognostic value. Evaluation of other potential biomarkers, including immune markers, is ongoing. Trial registration Registration number: NCT01120184 . Date of registration: April 28, 2010 (registered prospectively).